Operative Techniques in Laryngology - Rosen, Clark A.; Simpson, C. Blake; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Operative Techniques in Laryngology fills a void that currently exists in otolaryngology textbooks: a comprehensive text on laryngeal surgery that can be used by physicians to prepare for surgical cases. It contains explicit step-by-step descriptions of surgical procedures such that the reader can “learn to operate”. The surgical atlas is written by well-known experts with step-by-step surgical maneuvers for various laryngeal procedures encompass both microlaryngeal surgery and laryngeal framework surgery. Postoperative care and complications are also covered to round out the information needed by the surgeon in the perioperative period. The atlas is richly illustrated with photographic representations of all surgical steps and superb artwork illustrations to highlight the difficult three-dimensional anatomic concepts. In summary: This unique guide filled with “cookbook” descriptions of laryngeal surgical procedures provides a quick and simple reference for all surgeons interested in laryngological surgery.
Clinical Evaluation of Laryngeal Disorders -- Anatomy and Physiology of the Larynx -- Principles of Clinical Evaluation for Voice Disorders -- Videostroboscopy and Dynamic Voice Evaluation with Flexible Laryngoscopy -- Pathological Conditions of the Vocal Fold -- Glottic Insufficiency: Vocal Fold Paralysis, Paresis, and Atrophy -- Glottic and Subglottic Stenosis: Evaluation and Surgical Planning -- Nonsurgical Treatment of Voice Disorders -- Timing, Planning, and Decision Making in Phonosurgery -- Anesthesia and Airway Management for Laryngeal Surgery -- Phonomicrosurgery for Benign Laryngeal Pathology - Fundamentals of Phonomicrosurgery -- Principles of Phonomicrosurgery -- Perioperative Care for Phonomicrosurgery -- Management and Prevention of Complications Related to Phonomicrosurgery -- Principles of Laser Microlaryngoscopy -- Principles of Vocal Fold Augmentation -- Phonomicrosurgery for Benign Laryngeal Pathology - Phonomicrosurgical Voice Procedures -- Vocal Fold Polyp -- Vocal Fold Nodules -- Vocal Fold Cyst and Vocal Fold Fibrous Mass -- Polypoid Corditis -- Vocal Fold Granuloma -- Vocal Fold Leukoplakia and Hyperkeratosis -- Surgical Treatment of Recurrent Respiratory Papillomatosis of the Larynx -- Surgical Management of Vocal Fold Vascular Lesions -- Vocal Fold Scar and Sulcus Vocalis -- Endoscopic Management of Teflon Granuloma -- Endoscopic Excision of Saccular Cyst -- Anterior Glottic Web -- Phonomicrosurgery for Benign Laryngeal Pathology - Laser Microlaryngeal Surgery (Airway/Neoplastic Conditions) -- Bilateral Vocal Fold Paralysis -- Posterior Glottic Stenosis: Endoscopic Approach -- Subglottic/Tracheal Stenosis: Laser/Endoscopic Management -- Carcinoma of the Vocal Fold -- Phonomicrosurgery for Benign Laryngeal Pathology - Laryngeal Injection Techniques -- Vocal Fold Augmentation via Direct Microlaryngoscopy -- Superficial Vocal Fold Injection -- Peroral Vocal Fold Augmentation in the Clinic Setting -- Percutaneous Vocal Fold Augmentation in the Clinic Setting -- Botulinum Toxin Injection of the Larynx -- Laryngeal Framework Surgery -- Principles of Laryngeal Framework Surgery -- Perioperative Care for Laryngeal Framework Surgery -- Silastic Medialization Laryngoplasty for Unilateral Vocal Fold Paralysis -- GORE-TEX® Medialization Laryngoplasty -- Arytenoid Adduction -- Cricothyroid Subluxation -- Translaryngeal Removal of Teflon Granuloma -- Excision of Combined Laryngocele -- Repair of Laryngeal Fracture -- Glottic and Subglottic Stenosis: Laryngotracheal Reconstruction with Grafting -- Glottic and Subglottic Stenosis: Cricotracheal Resection with Primary Anastomosis -- Tracheal Stenosis: Tracheal Resection with Primary Anastomosis -- The Gray Minithyrotomy for Vocal Fold Scar/Sulcus Vocalis.
Keywords: Surgery; Otorhinolaryngology; Oral surgery; Maxillofacial surgery; Surgery; Otorhinolaryngology; Oral and Maxillofacial Surgery